Connect, BTS: An Example of Innovative Transmedia Branding To Rethink Spatiality and Meaning-making - Stefania Piccialli (Asia Marketing Journal, 2021)
This case study research analyzes the cross-artistic project Connect, BTS and its relationship to transmedia branding, meaning-making and spatiality. After an overview of the argument and a section on methodology, the reader will find the analysis of the case study. Thanks to the use of a qualitative approach, this examination of Connect, BTS unveils the ways in which this initiative becomes a location that allows a reconceptualization of space that fosters plurality, exchange, and subjectivity. Connect, BTS unites seemingly incompatible fields under one project, favoring the co-creation of meanings among different artists, BTS, ARMY (the group’s fans), business partners and viewers. This process has been investigated through content analysis, exploring Connect, BTS’s transmedia strategies from branding to storytelling, to evaluate their efficacy in regard to brand identity, brand experience, and brand trust. The paper will also explore the variety of layers and spatial dimensions contained in Connect, BTS, which flow from art to the music industry, material and digital space, various market sectors and media. In light of this, Connect, BTS embraces a galaxy of separate semantic units into an extended liminal continuum that does not discount difference.